Determining the Severity of Atopic Dermatitis in Children Presenting in General Practice: An Easy and Fast Method - Marjolein G. Willemsen; Rosalinda W. C. van Valburg; Pauline C. Dirven-Meijer; Arnold P. Oranje; Johannes C. van der Wouden; Heleen Moed (Dermatology Research and Practice)
Assessment of the severity of atopic dermatitis (AD) is necessary to evaluate the disease process. This study evaluates and validates the TIS in children with AD presenting in general practice. Independent investigators determined the severity of AD using the TIS and the objective SCORAD. The interobserver agreement for the TIS and SCORAD was calculated, as was the correlation between TIS and SCORAD. The mean time to assess the TIS was less than one minute. A moderate-to-good agreement between the observers was found for the TIS (κ=0.604 or 0.464), or SCORAD (κ=0.695 or 0.700). There was an excellent correlation between TIS and SCORAD (rs=0.755–0.839). In conclusion, the TIS is an easy and fast method to score AD. Because of the moderate to good interobserver agreement and the high correlation with the SCORAD, we recommend the TIS to determine the severity of AD in general practice.